Phorneroids A–M, diverse types of diterpenoids from Euphorbia neriifolia. (June 2022) - Gao, Yuan; Zhou, Jun-Su; Liu, Hong-Chun; Zhang, Yan; Yin, Wei-Hang; Liu, Qun-Fang; Wang, Guan-Wu; Zhao, Jin-Xin; Yue, Jian-Min
Abstract: A chemical investigation on the aerial parts of Euphorbia neriifolia led to the identification of thirteen undescribed diterpenoids, phorneroids A–M, including ent -abietane (A–D), ent -kaurane (E–G), ent -atisane (H–K), and ent -isopimarane (L and M) types, together with three known compounds. Phorneroid A represents the first example of 8-spiro-fused 9, 10- seco - ent -abietane diterpenoid lactone featuring a unique 6/5/6/5 spirocyclic framework. Biological assays showed that some of the compounds displayed moderate cytotoxicity against two human tumor cell lines, A549 and HL-60. Graphical abstract: Thirteen undescribed diterpenoids, including four types, along with three known analogues were isolated from Euphorbia neriifolia, and some of them showed cytotoxicity against the tested two human tumor cell lines. Image 1 Highlights: Thirteen undescribed diterpenoids were isolated from Euphorbia neriifolia. Four types ( ent -abietane, ent -kaurane, ent -atisane, and ent -isopimarane) are reported. Phorneroid A is the first 8-spiro-fused 9, 10- seco - ent -abietane diterpenoid lactone. Six diterpenoids exhibited cytotoxicity against A549 and HL-60 cell lines.